PREVALENCE OF VIOLENT SEXUAL ASSAULT ON SOUTH WEST NIGERIA GIRLS - Odu Bimbolakemi; Falana Bernard Akinlabi; Olotu Olukoyaadewale (European Scientific Journal, ESJ, 2014)
The study investigated the prevalence of violent Sexual Assault on South West Nigeria girls. It investigated the etiological and causative factors engendering sexual assault, characteristics of males that sexually assault and reasons why rapists assault. Also, myths about sexual assault, conditions that precipitates sexual assault, predicaments of sexual assault and intervention or needs of sexually assaulted survivors. Descriptive research design of the survey type was used in the study; the researcher surveyed the entire vulnerable female girls in South West Nigeria. Reports in national dailies and various sophisticated media indicated that majority of the girls are sexually abused and vulnerable to sexual assault. There are cultural, mythical, social and psychological factors enhancing the susceptibility of female children to sexual assault. There are indications that socio economic variables enhance the amenability of girls to sexual assault. Based on this, parents, teachers and significant others should orientate vulnerable girls and discourage cultural norms that engenders sexual assault. The law enforcement agents should sharpen all their weapons of sanitation to curb the prevalence of sexual assault in the society. The curriculum planners should imbibe this in the curriculum subjects and discourage the tenacity of assault. The study will be of benefit to vulnerable girls, parents, students, teachers, counsellors,law enforcement agents and care givers.